Constraints to obtaining consistent annual yields in perennial tree crops. I Heavy fruit load dominates over vegetative growth - Smith, Harley M (Plant science : an international journal of experimental plant biology, 2013)
Copyright © 2013 Elsevier Ireland Ltd. All rights reserved.